Improving Students' Creative Thinking Skills on Exponential Function Material Through the Application of the Discovery Learning Model - Nasrulloh, Muhammad Farid; Khuzaini, Nanang; Dyah Hestiana, Annisa; Umardiyah, Fitri (Universitas Mercu Buana Yogyakarta, 2025)
The study aims to determine the process and influence of creative thinking skills of class X students of SMK Kreatif Bahrul Ulum before and after implementing the discovery learning model. The research method used is pre-experimental design with one-group pretest-posttest design and using a quantitative approach. The subjects of this study were class X students of SMK Kreatif Bahrul Ulum Tambakberas. The research instruments used were tests and non-tests. The test instrument was in the form of pretest and post-test essay questions to measure students' creative thinking skills using discovery learning. The data analysis technique used was hypothesis testing. The data obtained were first tested for normality and homogeneity. Based on the calculation of the paired sample t test, it showed that the t count value was 19.453 with a significance of 0.000. The significance value shows 0.000 <error level of 0.05, so it can be concluded that Ha is accepted. So it can be concluded that there is an increase in the creative thinking skills of class X students of SMK Kreatif Bahrul Ulum Tambakberas before and after implementing the discovery learning model.